Modelling green sukuk in the ASEAN Region - Philippines - Ong, Princess Riza G. (Animo Repository, 2023)
The Philippine housing backlog continues to accumulate, despite projects launched by previous administrations. The government has been using the national budget to address this need, but the approved budget has not been enough to provide decent, affordable, and climate-resilient housing to a significant number of homeless and underprivileged Filipino families. One way to address the housing backlog is to issue bonds. However, simply building more houses will not address the problem. The houses must be of high quality and meet international standards of decency and resiliency. In addition, the government must work with private home developers to increase the supply of housing. Another way to address the housing backlog is to issue green bonds. Green bonds are a type of bond that is used to finance projects that have environmental benefits. Issuing green bonds would enable the government to raise capital for projects that will help to address the housing backlog while also protecting the environment. Tapping foreign and domestic investors for funding would be more attractive if the government were to issue sukuk. Sukuk is a type of Islamic bond that is compliant with Shariah law. Shariah is a religious law that is followed by Muslims. Issuing sukuk would open a new source of funding for the government and would help to address the housing backlog. Introducing a green sukuk to address the Philippine housing backlog would be a pioneering development in both the housing sector and the capital markets. It would provide opportunities for both investors and issuers to encourage sustainable and inclusive growth while leading the investment community and the country to progress.